From Temporary Fixes to Informed Decisions—Design Echelons for Evaluating Workarounds - Reineke, Malte Fabian; Löhr, Bernd; Aßbrock, Agnes; Bartelheimer, Christian; Beverungen, Daniel (International Conference on Business Process Management 2025)

Are numerical or verbal explanations of AI the key to appropriate user reliance and error detection? - Papenkordt, Jörg; Ngonga Ngomo, Axel-Cyrille; Thommes, Kirsten (Behaviour & Information Technology)

Shifting Dynamics: How Generative AI as a Boundary Resource Reshapes Digital Platform Governance - Mayer, Anne-Sophie; Kostis, Angelos; Strich, Franz; Holmström, Jonny (Journal of Management Information Systems)

Distributed and Parallel Low-Diameter Decompositions for Arbitrary and Restricted Graphs - Dou, Jinfeng; Götte, Thorsten; Hillebrandt, Henning; Scheideler, Christian; Werthmann, Julian (16th Innovations in Theoretical Computer Science Conference (ITCS 2025))

Inertial dynamics with vanishing Tikhonov regularization for multobjective optimization - Bot, Radu Ioan; Sonntag, Konstantin (Journal of Mathematical Analysis and Applications)
In this paper we introduce, in a Hilbert space setting, a second order dynamical system with asymptotically vanishing damping and vanishing Tikhonov regularization that approaches a multiobjective optimization problem with convex and differentiable components of the objective function. Trajectory solutions are shown to exist in finite dimensions. We prove fast convergence of the function values, quantified in terms of a merit function. Based on the regime considered, we establish both weak and, in some cases, strong convergence of trajectory solutions toward a weak Pareto optimal solution. To achieve this, we apply Tikhonov regularization individually to each component of the objective function. This work extends results from single objective convex optimization into the multiobjective setting.
Keywords: Pareto optimization; Lyapunov analysis; gradient-like dynamical systems; inertial dynamics; asymptotic vanishing damping; Tikhonov regularization; strong convergence

Promote technology learning using a spiral curriculum – Developing evidence-based concepts for technology education focusing on problem-solving - Schemel, Nele; Tenberge, Claudia (The 42nd Pupils' Attitudes Towards Technology Conference Proceedings 2025)

‚Novellierungen‘ der Novellistik. Der ‚Fall‘ der Novelas ejemplares - Schlieper, Hendrik (Artes)

Auffächerung im Spiegel der Übersetzung und darüber hinaus: La Grande Peur dans la montagne von Charles Ferdinand Ramuz und die beiden deutschen Übersetzungen dieses Romans - Kunert, Irene Dorothea (PhiN Beiheft 40: Verdichtung und Auffächerung. (Übersetzte) Literatur zwischen Präsenz und Virtualität)

Teacher shortage in Germany - overview and insights - Jonas-Ahrend, Gabriela; Tenberg, Ralf (Journal of Education for Teaching)

Was im Gedicht geschieht: Jan Wagner. Paderborn Wintersemester 2023/24. 42. Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller

Counting of Teams in First-Order Team Logics - Haak, Anselm; Kontinen, Juha; Müller, Fabian; Vollmer, Heribert; Yang, Fan (ACM Transactions on Computational Logic)
We study descriptive complexity of counting complexity classes in the range from #P to \({\text{#}\!·\!\text{NP}}\) . The proof of Fagin’s characterization of NP by existential second-order logic generalizes to the counting setting in the following sense: The class #P can be logically described as the class of functions counting satisfying assignments to free relation variables in first-order formulae. This was first observed by Saluja et al. (1995). In this paper we extend this study to classes beyond #P and extensions of first-order logic with team semantics. These team-based logics are closely related to existential second-order logic and its fragments, hence our results also shed light on the complexity of counting for extensions of first-order logic in Tarski’s semantics. Our results show that the class \({\text{#}\!·\!\text{NP}}\) can be logically characterized by independence logic and existential second-order logic, whereas dependence logic and inclusion logic give rise to subclasses of \({\text{#}\!·\!\text{NP}}\) and #P , respectively. We further relate the class obtained from inclusion logic to the complexity class \({\text{TotP}} \subseteq{\text{#P}}\) .

C1-Smooth Parametrization of Polynomial Shapes over Polygonal Domains - Khanteimouri, Payam; Campen, Marcel (Proceedings of the 2025 SIAM International Meshing Roundtable)

Can AI Regulate Your Emotions? An Empirical Investigation of the Influence of AI Explanations and Emotion Regulation on Human Decision-Making Factors - Lammert, Olesja (Communications in Computer and Information Science)
Abstract Research indicates that anger is a prevalent emotion in human-technology interactions, often leading to frustration, rejection and reduced trust, significantly impacting user experience and acceptance of technology. Particularly in high-risk or uncertain situations, where AI explanations are intended to help users make more informed decisions, decision-making is influenced by emotional factors, impairing understanding and leading to suboptimal choices. While XAI research continues to evolve, greater consideration of users’ emotions and individual characteristics remains necessary. Broadening empirical studies in this area could foster a more comprehensive understanding of decision-making processes following explanations, especially in relation to the interaction between emotions and cognition. In response, this study seeks to contribute to this area by employing an experimental design to examine the effects of AI explanations and emotion regulation on user reliance and trust of emotional users. The results provide a foundation for future human-centered research in XAI, focusing on the impact of emotions and cognition in human-technology interactions.

Accounting for Unintended Consequences in IS Research: A Call to Action - Benbya, Hind; Strich, Franz; Trieu, Van-Hau (Australasian Journal of Information Systems)
Unintended consequences in Information Systems (IS) research are typically examined only after they have surfaced in practice, often treated as isolated instances rather than being systematically identified and understood. This reactive stance constrains our ability to anticipate risks, recognize emerging opportunities, and build cumulative insights across studies. To assess the current state of IS research on unintended consequences, we conducted a scoping review of literature in the Association for Information Systems' Senior Scholars' Basket of Journals. Our review highlights significant gaps in how unintended consequences are defined, theorized, and systematically compared. To address these gaps, we propose three foundational considerations: (1) conceptual clarity, to refine definitions and delineate boundaries; (2) relational configurations, to analyze the interplay between actors, technologies, and contexts; and (3) temporal configurations, to capture the evolving nature of consequences over time. Building on these dimensions, we introduce a set of guiding questions designed to provide shared analytical vocabulary rather than a prescriptive framework. These questions enable researchers to more systematically identify, categorize, and compare unintended consequences across contexts, thereby fostering theoretical precision, facilitating cross-contextual learning, and supporting a more anticipatory and comprehensive understanding of the phenomenon.

Overview on Threshold Signature Schemes and their Applications - Anonymous, A.

Comparison of Time-Lock Puzzle Constructions and Their Security - Anonymous, A

Damage-incorporated four-step mean-field method for simulating CFRP machining: a novel algorithmic approach - Zhan, Yingjie; Caylak, Ismail; Ostwald, Richard; Barth, Enrico; Uhlmann, Eckart (Multiscale and Multidisciplinary Modeling, Experiments and Design)

Unraveling the head-fake effect: Dynamic measures of cognitive conflict in sport contexts - Güldenpenning, Iris; Schulze Freilinghaus, Lars; Böer, Nils Tobias; Weigelt, Matthias (57. Herbsttagung experimentelle Kognitionspsychologie (HexKop))

Mercedes. Gunst und Affekt in Cervantes’ La española inglesa - Schlieper, Hendrik (Artes)

Look Who's Talking: Multivoicedness in Students’ Descriptions of Their Disciplines - Schmöckel, Sabrina